State and origin of the present-day stress field in sedimentary basins: New results from the World Stress Map Project. - Tingay, Mark; Muller, B.; Reinecker, J.; Heidbach, O. (Curran Associates, 2006)
The present-day stress field provides fundamental insight into the forces driving plate tectonics and intra-plate deformation. Furthermore, knowledge of the in situ state of stress is essential in petroleum and mining geomechanics applications such as the stability of boreholes and tunnels, and improving production through natural and induced fractures. The World Stress Map (WSM) Project has, for 20 years, compiled a public global database of present-day tectonic stress information to determine and understand the state of stress in the Earth's lithosphere. The WSM database has revealed that plate-scale stress fields are controlled by forces exerted at plate boundaries (e.g. mid-ocean ridges, continental collision zones), commonly resulting in regional stress orientations approximately parallel to plate motion. However, the state and origin of present-day stress fields at smaller scales, such as within sedimentary basins, remain poorly understood in comparison. The WSM Project commenced its new 'Present-day Stress in Sedimentary Basins' initiative in 2004 to investigate the state of stress in sedimentary basins and the controls on smaller scale stress fields. Detailed analysis of present-day stresses within sedimentary basins commonly reveals significant and complex variations in the present-day stress orientation, both across basins and within fields.For example, borehole breakouts in the North German Basin and the Baram Delta province of Brunei (northwest Borneo) indicate broad regional rotations in the maximum horizontal stress orientation. The present-day maximum horizontal stress orientations in the Gulf of Thailand are approximately north-south at the basin-scale (perpendicular to plate motion) and are perturbed locally to be approximately parallelto fault strike. The Permian Basin of Texas and New Mexico displays widely varying stress orientations between fields, with some neighbouring fields exhibiting perpendicular stress orientations. The WSM database now contains information from approximately 70 sedimentary basins, enabling a unique insight into controls on stresses in the oil patch. Basin- and field-scale stress fields result from the complex combination of numerous factors acting at different scales, including far-field forces (e.g. plate boundary forces), basin geometry (e.g. the shape of deltaic wedges), geological structures (e.g. diapirs, faults), mechanical contrasts (e.g. evaporites, overpressured shales, detachment zones), topography and deglaciation.